The functional status of vestibular otolith and conductive pathway in patients with unilateral idiopathic sudden sensorineural hearing loss - Shen, Jiali; Ma, Xiaobao; Zhang, Qing; Chen, Jianyong; Wang, Lu; Wang, Wei; He, Kuan; Sun, Jin; Zhang, Qin; Chen, Xiangping; Duan, Maoli; Jin, Yulian; et al. (Frontiers in Neurology, 2023)
The cause of idiopathic sudden sensorineural hearing loss (ISSNHL) remains unknown. It has been found that the functional status of vestibular otolith is relevant to its prognosis, however, the evaluation of vestibular otolith (intra-labyrinth) and superior and inferior vestibular nerve pathway (retro-labyrinth) in ISSNHL patients is not well documented.Objective: To investigate the functional status of vestibular otolith and conductive pathway in patients with unilateral ISSNHL and analyze the correlations between vestibular evoked myogenic potentials (VEMPs) and hearing improvement after treatment.Methods: 50 patients with unilateral ISSNHL underwent a battery of audio-vestibular evaluation, including pure tone audiometry, middle ear function, air conducted soundcervical VEMP (ACS-cVEMP), ACS-ocular VEMP (ACS-oVEMP), Galvanic vestibular stimulation-cervical VEMP (GVS-cVEMP) and GVS-ocular VEMP (GVS-oVEMP). The results of auditory and VEMPs were retrospectively analyzed.The abnormal rates of ACS-cVEMP, ACS-oVEMP, GVS-cVEMP and GVS-oVEMP in affected ears were 30%, 52%, 8% and 16%, respectively. In affected ears, the abnormal rate of ACS-oVEMP was significantly higher than that in ACS-cVEMP (p=0.025), while it was similar between GVS-cVEMP and GVS-oVEMP (p=0.218).Compared with GVS-cVEMP, affected ears presented with significantly higher abnormal rate of ACS-cVEMP (p=0.005), and the abnormal rate of ACS-oVEMP was significantly higher than that in GVS-oVEMP (p＜0.001). No significant difference existed in latency and amplitude between affected and unaffected ears in ACS-VEMPs or GVS-VEMPs (p＞0.05). The abnormal rate of VEMPs in poor recovery group was significantly higher than good recovery group (p=0.040). The abnormality percentage of ACS-oVEMP and GVS-oVEMP in poor recovery group were significantly higher than that in good recovery group (p=0.004 and 0.039, respectively). The good hearing recovery rates were 76.47% in normal VEMPs group, 58.33% in intra-labyrinth lesion group, and 22.22% in the retro-labyrinth lesion group. Hearing recovery worsened as a greater number of abnormal VEMPs presented.Besides the Corti's organ, the impairment of otolithic organs was prominent in patients with ISSNHL. The normal VEMPs group had the highest rate of good recovery, followed by intra-labyrinth lesion group, and the retro-labyrinth lesion group presented with the lowest recovery rate. Abnormality in ACS-oVEMP and/or GVS-oVEMP were indicators of poor prognosis.